Self-host thermally activated delayed fluorescent dendrimers with flexible chains: an effective strategy for non-doped electroluminescent devices based on solution processing. Issue 37 (8th September 2016) - Ban, Xinxin; Jiang, Wei; Lu, Tingting; Jing, Xiaofang; Tang, Qifeng; Huang, Suli; Sun, Kaiyong; Huang, Bin; Lin, Baoping; Sun, Yueming
Abstract : Due to the encapsulation of the emissive core, the concentration quenching effect of the TADF material can be effectively restrained. Abstract : Two self-host dendrimers TZ-Cz and TZ-3Cz with TADF nature were designed and synthesized for solution-processed nondoped fluorescent organic light-emitting diodes (OLEDs). The first and second generation carbazole dendrons were conveniently introduced into the TADF core through non-conjugated aliphatic chains, which favourably make the fluorescence of the core independent of the peripheral dendrons. Photophysical investigation showed that the prevalent concentration quenching effect of the TADF materials can be effectively restrained by the encapsulation of the emissive core. Moreover, the key role of the end-capping moieties on the molecular frontier orbital of the dendrimers was revealed by electrochemical testing and theoretical calculations. Solution-processed OLEDs featuring TZ-3Cz as the host-free emitter achieved a superior external quantum efficiency of 10.1%, which is almost ten times higher than that of the emissive core TZ (1.09%). Thus, a facile strategy to design a solution-process with highly emissive self-host TADF materials for nondoped OLEDs by flexible alkyl chain is demonstrated.